1990
DOI: 10.1007/bf00133896
|View full text |Cite
|
Sign up to set email alerts
|

Comparing conventional and resource based education in chemical engineering: student perceptions of a teaching innovation

Abstract: Abstracl. While the adoption of resource based education (RBE) in the teaching of individual engineering subjects is not novel, the introduction of RBE throughout an entire university department is unprecedented. The purpose of this longitudinal study with second year Chemical Engineering students (n = 31) was to detect, quantify and describe the consequences for teaching and learning of some concerns that had arisen in students as a result of the introduction of RBE. These concerns appeared to pose some formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Examining experience rather than beliefs alone, Baxter (1990) reported student judgements that the most negative feature of two out of three completely RBL-focused courses investigated was reduced teacher-student contact. Lack of feedback on assessment, and lack of opportunity to discover what standard was required, were of particular concern to students.…”
Section: Background and Rationalementioning
confidence: 92%
See 1 more Smart Citation
“…Examining experience rather than beliefs alone, Baxter (1990) reported student judgements that the most negative feature of two out of three completely RBL-focused courses investigated was reduced teacher-student contact. Lack of feedback on assessment, and lack of opportunity to discover what standard was required, were of particular concern to students.…”
Section: Background and Rationalementioning
confidence: 92%
“…Kiesler & Sproull (1987) also report higher than 70% of positive attitudes towards computing on all measures in their questionnaire sample of faculty and students. Baxter (1990) suggests that if major learning dif culties associated with RBL are reduced via the development of high quality human and physical resources, it has a unique potential to support the development of independent learning.…”
Section: Background and Rationalementioning
confidence: 98%
“…The introduction of resource based education, however, may lead to other problems [22]. In a longitudinal study with second year chemical engineering students, more study problems with resource based education were encountered than under conventional engineering education.…”
Section: The Relationship Between Instruction and Skill Developmentmentioning
confidence: 96%
“…They did summarize two studies of sophomore chemical engineering courses. The first study [17] found that student performance improved when Resource Based Education (i.e. computer-aided learning packages, software tools, etc.)…”
Section: Comparison Of Student Learning In Physical and Simulated Unimentioning
confidence: 99%